Development of a novel sulfonate ester-based prodrug strategy. Issue 2 (15th January 2016) - Hanaya, Kengo; Yoshioka, Shohei; Ariyasu, Shinya; Aoki, Shin; Shoji, Mitsuru; Sugai, Takeshi
Graphical abstract: Abstract: A self-immolative γ-aminopropylsulfonate linker was investigated for use in the development of prodrugs that are reactive to various chemical or biological stimuli. To demonstrate their utility, a leucine-conjugated prodrug of 5-chloroquinolin-8-ol (5-Cl-8-HQ), which is a potent inhibitor against aminopeptidase from Aeromonas proteolytica (AAP), was synthesized. The sulfonate prodrug was considerably stable under physiological conditions, with only enzyme-mediated hydrolysis of leucine triggering the subsequent intramolecular cyclization to simultaneously release 5-Cl-8-HQ and form γ-sultam. It was also confirmed that this γ-aminopropylsulfonate linker was applicable for prodrugs of not only 8-HQ derivatives but also other drugs bearing a phenolic hydroxy group.